ANÁLISE, PROJETO E IMPLEMENTAÇÃO DE DRIVERS DE POTÊNCIA TIPO PONTE H PARA APLICAÇÃO EM AUTOMÓVEIS ELÉTRICOS - Turchiello, Gilson; Reimbold, Manuel M. P.; Kotlinski, Eliseu; Capinos, César U. (Salão do Conhecimento, 2013)
Resumo